Outcomes of single physician-modified fenestrated stent grafts for endovascular repair of thoracic aortic lesions involving the distal aortic arch. (13th December 2020) - Zhu, Jiechang; Ma, Chao; Dai, Xiangchen; Wang, Zheng; Fan, Hailun; Feng, Zhou; Luo, Yudong; Zhang, Yiwei; Hu, Fanguo
Abstract: OBJECTIVES: Our goal was to evaluate the outcomes of fenestrated thoracic endovascular aortic repair of thoracic aortic lesions involving the distal aortic arch using single physician-modified stent grafts. METHODS: This single-centre, retrospective study included 58 consecutive patients (mean age, 57 ± 14 years; 11 women) who underwent fenestrated thoracic endovascular aortic repair for thoracic aortic pathologies involving the distal aortic arch using single physician-modified stent grafts between November 2015 and December 2018. Indications included complicated acute type B dissection or intramural haematoma with an unfavourable proximal landing zone ( n = 49), type Ia endoleak subsequent to thoracic endovascular aortic repair due to acute type B dissection ( n = 1) and distal arch degenerative aneurysms <15 mm from the left subclavian artery ( n = 8). RESULTS: The technical success rate was 94.8%. The 30-day mortality was 1.7%, and the perioperative ischaemic stroke rate was 1.7%. The incidence of perioperative complications was 10.3%. At a mean follow-up of 26.3 months (range, 7–44), all target vessels were patent. All-cause mortality was 5.2%. Estimated 1-, 2- and 3-year survival was 98.3 ± 1.7%, 96.4 ± 2.5% and 93.2 ± 3.9%, respectively. CONCLUSION: The single fenestrated stent graft technique is feasible and effective for endovascular repair of thoracic aortic pathologies involving the distal aortic arch.